ASEAN DALAM MENJAGA STABILITAS KEAMANAN REGIONAL (Study kasus: Polusi Asap Kebakaran Hutan Indonesia) - , Dian Azmawati, SIP.; , Dra. Ilien Halina, M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims at analyzing the influence of new security approach from the traditional to human security approach towards the security cooperation in ASEAN. This research used the transboundary haze pollution caused by Indonesian forest fires as the threat to human security in South East Asia. This devastating haze pollution was caused by land and forest fires in Indonesian territory on Borneo and Sumatera, deliberately started by plantation owners seeking to clear forests for commercial use and worsened by the prolonged drought. Unfortunately the fires in Indonesia have severely affected its neighbors particularly Brunei Darussalam, Malaysia, Singapore, Thailand, and the Philippines. The haze became threat to the health of people and economic activities. The research finding is that the ASEAN security cooperation ths far could minimize the cause of threat and successfully distributed aids to the affected countries.